Non-invasive techniques to assess restrictive lung disease in workers exposed to free crystalline silica: Lung Restriction and Exposure to Free Crystalline Silica in Clay Niche’s Working - Corradi, Massimo; Folesani, Giuseppina; Robuschi, Benedetta; Selis, Luisella; Riccelli, Maria Grazia; Riccelli, Maria Grazia; Andreoli, Roberta; Pisi, Roberta; Chetta, Alfredo; Mutti, Antonio (La Medicina del Lavoro, 2019)
Objectives: To compare the reliability of spirometry and body plethysmography in detecting restrictive lung disease in clay excavation workers exposed to free crystalline silica (FCS). The exhaled breath condensate (EBC) biomarkers of oxidative stress were also assessed in order to evaluate early lung damage. Methods: The study involved 62 workers (58 males and 4 females) at a company that extracts and processes clay. Results: Body plethysmography (total lung capacity below the lower normal limit) and spirometry respectively indicated restrictive pattern prevalence rates of 22.6% and 1.6%. EBC 4-hydroxynonenale levels were not sufficiently sensitive to highlight a restrictive deficit, but did distinguish low and high rates of occupational exposure. There was no correlation between plethysmography values and the intensity or duration of exposure. Conclusions: Only one out of 14 cases of restrictive deficit diagnosed on the basis of body plethysmography values was also identified by means of spirometry. This finding supports the need to use body plethysmography in the health surveillance of clay workers exposed to FCS.